A Syntactical Analysis of 'oun' in Papyrus 66 - Rogers, Trent (Filología neotestamentaria, 2012)
Greek particles are often overlooked in the interpretation and translation of ancient texts, but a better understanding of their syntactical functions aids in understanding the relationships among clauses and results in a better understanding of the texts’ meanings. This article examines the use of oun in Papyrus 66, provides examples and explanations of the different uses, and categorizes every occurrence in the Gospel of John. It clarifies established uses and paves new ground by locating the comparative use. Moreover, it notices a dialogical pattern wherein lego + oun serves as an alternative to apokrinomai (kai lego), and in this pattern, asyndeton with lego may convey increased markedness.